8.5k views
5 votes
Use the formulas for lowering powers to rewrite the expression in terms of the first power of cosine.

cos^4 x sin^2 x

User Zamicol
by
4.5k points

1 Answer

4 votes

The key identity is


\cos^2x=\frac{1+\cos2x}2

We have


\cos^4x\sin^2x=\cos^4x(1-\cos^2x)


=\cos^4x-\cos^6x


=\left(\frac{1+\cos2x}2\right)^2-\left(\frac{1+\cos2x}2\right)^3


=\frac{1+\cos2x-\cos^22x-\cos^32x}8

Then


\cos^22x=\frac{1+\cos4x}2

and


\cos^32x=\cos2x\cos^22x=\frac{\cos2x(1+\cos4x)}2


\cos^32x=\frac{\cos2x+\frac{\cos6x+\cos2x}2}2=\frac{3\cos2x+\cos6x}4


\cos^4x\sin^2x=\frac{1+\cos2x-\frac{1+\cos4x}2-\frac{3\cos2x+\cos6x}4}8


=(2+\cos2x-2\cos4x-\cos6x)/(32)

User Diegodsp
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.